2011
DOI: 10.1038/labinvest.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of alveolar epithelial type II progenitor cells from adult human lungs

Abstract: Resident stem/progenitor cells in the lung are important for tissue homeostasis and repair. However, a progenitor population for alveolar type II (ATII) cells in adult human lungs has not been identified. The aim of this study is to isolate progenitor cells from adult human lungs with the ability to differentiate into ATII cells. We isolated colony-forming cells that had the capability for self-renewal and the potential to generate ATII cells in vitro. These undifferentiated progenitor cells expressed surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 47 publications
3
93
0
1
Order By: Relevance
“…Alveolar progenitor cells (AEPCs) isolated from human lungs, c-kit-positive cells, and E-Cadherin and leucinerich repeat-containing G-protein-coupled receptor 6 double positive (E-Cad/Lgr6 + ) cells might have the potential for differentiation into lung specific lineages. 58,59 Fujino and colleagues demonstrated that AEPCs have an epithelial phenotype with an MSC character. According to microarray analysis, AEPCs share many genes with AETII cells and mesenchymal stem cells, which suggests an overlapping phenotype with both the alveolar epithelium and the mesenchyme in these cells.…”
Section: Stem/progenitor Cells and Mixed Cell Repopulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alveolar progenitor cells (AEPCs) isolated from human lungs, c-kit-positive cells, and E-Cadherin and leucinerich repeat-containing G-protein-coupled receptor 6 double positive (E-Cad/Lgr6 + ) cells might have the potential for differentiation into lung specific lineages. 58,59 Fujino and colleagues demonstrated that AEPCs have an epithelial phenotype with an MSC character. According to microarray analysis, AEPCs share many genes with AETII cells and mesenchymal stem cells, which suggests an overlapping phenotype with both the alveolar epithelium and the mesenchyme in these cells.…”
Section: Stem/progenitor Cells and Mixed Cell Repopulationmentioning
confidence: 99%
“…According to microarray analysis, AEPCs share many genes with AETII cells and mesenchymal stem cells, which suggests an overlapping phenotype with both the alveolar epithelium and the mesenchyme in these cells. 58 Kajstura and colleagues isolated c-kit-positive cells from adult human lungs and when the cell population was injected into injured lungs of C57BL/6 mice, the cells differentiated not only into epithelial cells, but also into mesenchymal and endothelial cells without rejection. 59 …”
Section: Stem/progenitor Cells and Mixed Cell Repopulationmentioning
confidence: 99%
“…The gaseous alveolar surface is lined by alveolar type I cells (AT-I) and alveolar type II cells (AT-II) [6]. Recent studies have characterized resident alveolar stem cells in human [7]. However, potent regenerative compounds have not been identified for human alveolar stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…85,86 Some adenocarcinomas have shown a phenotype similar to that of alveolar epithelial progenitor cells. 75 These data suggest that some lung cancer cells have stem cell characteristics and thus may be cancer stem cells. Further research is needed in this area.…”
Section: Lung Cancer Stem Cellsmentioning
confidence: 89%
“…Then, we isolated human alveolar progenitor cells (AEPCs) from the StemSurvive-preserved human lungs. 75 AEPCs represent an epithelial phenotype with mesenchymal stem cell character. According to microarray analyses, AEPCs share many genes with mesenchymal stem cells (MSCs) and ATII cells (Fig.…”
Section: Alveolar Epithelial Progenitor Cellsmentioning
confidence: 99%